The Practice of Pre-trial Detention in England & Wales - Changing Law and Changing Culture - Smith, Tom (European journal on criminal policy and research, 2022)
Pre-trial detention empowers criminal courts to imprison defendants before they have been convicted of an offence. This is a significant power which should be subject to a rigourous decision-making process. A 2016 study of pre-trial detention practice in England and Wales highlighted concerns about such processes, recommending changes to law and practice in that jurisdiction. In 2017, several of these recommendations became law. This article details a follow-up empirical study, conducted in 2020, which sought to examine the impact of these changes on day-to-day pre-trial detention practice in criminal courts. After analysing the data, the article concludes that the changes in fact had minimal impact on practice, and suggests that changing the law does not necessarily translate into a change in the culture of pre-trial detention practice.